L1 Processing of familiar Malay Idiomatic Phrases - Radina, Mohd Deli; Rosnah, Mustafa; Monaliza, Sarbini-Zin; Siti Marina, Kamil; Hamidah, Abdul Wahab (2014)
Psycholinguistic research in the area of figurative language processing has been carried out tremendously over the past few decades particularly involving idioms in the English language and other European languages. According to Cooper (1999), the meaning of an idiomatic expression does not always come from meaning of its individual components. For instance, in the idiom to kick the bucket, none of the individual words contribute to the actual idiom meaning to die. In Malay language, a figurative phrase that is similar in notion to an ‘idiom’ in English is known as Simpulan Bahasa (Charteris-Black, 2003). The unique characteristic of idiomatic phrases as having ‘fixed’ meanings different from their single words components has prompted the research into first language (L1) and second language (L2) processing of figurative phrases or sentences. Various models, thus, have been developed contesting issues of compositionality in idiom comprehension (Bobrow & Bell, 1973; Swinney & Cutler, 1979), modular versus parallel views on processing (Cacciari & Tabossi, 1988; Tittone & Connine, 1999) and literality against non-literality (Gibbs, 1980, 1986), amongst other things.